1999
DOI: 10.1002/stem.170242
|View full text |Cite
|
Sign up to set email alerts
|

Human Hematopoietic Stem/Progenitor Cells Generate CD5+B Lymphoid Cells in NOD/SCID Mice

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
16
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 73 publications
7
16
0
Order By: Relevance
“…In addition, it was reported recently that CD5 ϩ cells were found among CD19 ϩ B lymphoid cells in NOD/SCID mice injected with only cord blood. 23 This observation is in line with numerous reports that human cells expanded in NOD/SCID mice engrafted with cord blood alone are predominantly CD19 ϩ . 9,10,[16][17][18] The paucity of CD19 ϩ cells in the engrafted NOD/SCID mice suggests that the demonstration of CD5 ϩ CD7 ϩ cells in these mice is less likely be attributed to the expansion of this subset of CD5 ϩ CD19 ϩ doublestaining cells, as observed in Novelli et al 23 Instead, the results suggest that the expansion of the cells from engrafted cord blood Figure 5.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, it was reported recently that CD5 ϩ cells were found among CD19 ϩ B lymphoid cells in NOD/SCID mice injected with only cord blood. 23 This observation is in line with numerous reports that human cells expanded in NOD/SCID mice engrafted with cord blood alone are predominantly CD19 ϩ . 9,10,[16][17][18] The paucity of CD19 ϩ cells in the engrafted NOD/SCID mice suggests that the demonstration of CD5 ϩ CD7 ϩ cells in these mice is less likely be attributed to the expansion of this subset of CD5 ϩ CD19 ϩ doublestaining cells, as observed in Novelli et al 23 Instead, the results suggest that the expansion of the cells from engrafted cord blood Figure 5.…”
Section: Discussionsupporting
confidence: 89%
“…Ten weeks after transplantation, about 20% to 30% engrafted human cells in mouse BM retained the CD34 ϩ phenotypes, about 60% expressed a human B cell marker (CD19), and about 5% expressed a marker for mature myeloid cells (CD13). Consistent with previous reports, 51,52 more than 90% of the human cells in the BM of NOD/SCID mice of both groups were MHC II ϩ at 10 weeks after transplantation, including CD19 ϩ B lymphocytes (about 60%), CD34 ϩ cells (about 30%), and fewer CD13 ϩ cells ( Figure 3C). Cells expressing high-level GFP were found in all the expected human cell subsets in the NOD/SCID engraftment model, particularly in mice engrafted with EF.GFP-transduced CBSCs ( Figure 3C and Table 1).…”
Section: Preferential Transgene Expression In Mhc II ؉ Human Cells Ensupporting
confidence: 92%
“…We first used human cord blood stem cells (CBSCs) because they have higher engraftment capacity in this mouse model than PBSCs or BM CD34 ϩ cells. [12][13]16,[50][51][52] Cyropreserved CB CD34 ϩ cells were cultured overnight and transduced twice with DR.GFP or EF.GFP at the MOI of 60 in the next 2 days. Two days after the last transduction, GFP and CD34 expression of the transduced cells was examined by FACS analysis.…”
Section: Preferential Transgene Expression In Mhc II ؉ Human Cells Enmentioning
confidence: 99%
“…As others have found with this model (8,11,12,27), human hemopoietic cells preferentially expand within the B lymphocyte lineage. However, this is the first detailed investigation of all stages of B lymphopoiesis with a direct comparison to the replication and differentiation events that occur within normal marrow.…”
Section: Discussionsupporting
confidence: 82%
“…Our preliminary experiments revealed that survival and human cell chimerism were optimal with a low dose (100 cGy) of 137 Cs irradiation, and we confirmed that the majority of cells belonged to the B lymphocyte lineage (8,11,12,27). Human CD45 ϩ cells represented 39.4 Ϯ 17.6% of total bone marrow cells in these animals and 76.7 Ϯ 7.1% of them expressed CD19.…”
Section: Engraftment and Normal Differentiation Of Human Cells In Nodsupporting
confidence: 66%